2022
DOI: 10.3389/fgene.2022.971845
|View full text |Cite
|
Sign up to set email alerts
|

Gene co-expression network analysis revealed novel biomarkers for ovarian cancer

Abstract: Ovarian cancer is the second most common gynecologic cancer and remains the leading cause of death of all gynecologic oncologic disease. Therefore, understanding the molecular mechanisms underlying the disease, and the identification of effective and predictive biomarkers are invaluable for the development of diagnostic and treatment strategies. In the present study, a differential co-expression network analysis was performed via meta-analysis of three transcriptome datasets of serous ovarian adenocarcinoma to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…3,4 Multiple studies show that CNIH4 is expressed in many malignant tumors and participates in their development, invasion, and metastasis. [5][6][7][8] Therefore, CNIH4 may function as an oncogene. Mishra et al reported that TMED9 protein inhibits the enhancing effect of TMED3-WNT-TCF on colon cancer cell metastasis by promoting the CNIH4/TGF-α/GLI cascade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Multiple studies show that CNIH4 is expressed in many malignant tumors and participates in their development, invasion, and metastasis. [5][6][7][8] Therefore, CNIH4 may function as an oncogene. Mishra et al reported that TMED9 protein inhibits the enhancing effect of TMED3-WNT-TCF on colon cancer cell metastasis by promoting the CNIH4/TGF-α/GLI cascade.…”
Section: Introductionmentioning
confidence: 99%
“…It is located on the long arm of Chromosome 1, Region 4, Band 2, and sub‐band 3,4 . Multiple studies show that CNIH4 is expressed in many malignant tumors and participates in their development, invasion, and metastasis 5–8 . Therefore, CNIH4 may function as an oncogene.…”
Section: Introductionmentioning
confidence: 99%
“…suggests that POC1A may influence tumour progression and represent a potential therapeutic target for cancer 12 . Investigations by Ceyda Kasavi indicate that POC1A exhibits superior diagnostic capability for ovarian cancer and could serve as a candidate factor for diagnosis and treatment 13 . Yuma Wada et al.…”
Section: Introductionmentioning
confidence: 99%
“…The co-expression network of ncRNAs refers to the network of non-protein-coding RNA molecules involved in the regulation of gene expression in cells, reflecting the interaction and regulatory relationship between these ncRNA molecules, and their expression levels also show a certain correlation. Differential co-expression networks have been widely used to discover gene modules and hub genes in various cancers, such as ovarian cancer [ 19 ], retinoblastoma [ 20 ], and cervical cancer [ 21 ].…”
Section: Introductionmentioning
confidence: 99%